Time Series of Closed and Open Eyes Eeg Conditions Reveal Differential Characteristics in the Temporality of Linear and Non-Linear Analysis Domain - Diaz-Munoz, H (Elsevier B.V., 2018)
The basal states defined by the closed (EC) and open (EC) eyes conditions are revisited using linear and nonlinear analysis approaches. We compared EO and EC control states using standard Spearman R correlation between pairs of EEG electrodes. We also performed a moving correlation coefficient (MCC) analysis to explore the short-term (1-second) timeframe scale behavior of the synchronous/asynchronous dynamic of paired brain regions, and compared these results with the long-term correlation coefficient rendered from the complete 2 minutes EEG time series. In these two different (long- and short-) time scales, we also explored the nonlinear domain of chaos/order dynamic fluctuation. Using Hurst exponent as an estimator of the chaos/order balance of a time series, we studied the chaotic and self-organized (persistent) trends of the EEG signal coming from 8 subjects in closed and open eyes basal resting conditions. © 2018 The Authors. Published by Elsevier B.V.